2023
DOI: 10.1002/sstr.202300047
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Engineered Silica Shells on Gold Nanorods for Biomedical Applications

Abstract: Owing to their unique optical and chemical properties, gold nanorods (AuNRs) are among the most frequently used nanomaterials for biomedical applications, including cancer therapy, imaging, and drug delivery. In particular, the longitudinal dipole plasmon wavelength of AuNRs can be verified from the visible to the near‐infrared (NIR) region, allowing AuNRs to be used as photodynamic/photothermal and imaging contrast agents. At the same time, the silica shell is important as it enhances stability and facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 128 publications
1
19
0
Order By: Relevance
“…For example, at low temperature (<65 °C) and stirring, a large network is formed due to the slow rate of hydrolysis and condensation for silica formation, whereas higher temperature (60–80 °C) and vigorous stirring result in mesostructured particles in the nanometer range. It is reported that aggregated and large clumps of silica particles are formed beyond 80 °C of reaction temperature. ,, On the other hand, the slow rate of silicification at low acidity and high ionic strength is well documented in the literature. , Cationic surfactant CTAB assembled in a hexagonal array, which helps in creating 2D pores/channels with an interchannel distance of about 4 nm followed by base-catalyzed hydrolysis–condensation of an orthosilicate precursor (source of silica particle formation) for mesoporous silica network formation, which are characteristics of MCM-41 type silica. Silica nanoparticles are also prepared by using TEA as a sterically bulky chelating agent (pH stabilizer and as an additive) that controls the particle diameter . Later, surface modified mesoporous silica nanoparticles with various small molecules have been reported for biomedical applications, either imaging or therapeutics of cancer. , Silica is a well understood biomaterial and claimed as a safe material for preclinical and clinical studies. , Obviously, silica, especially MS, is inferior as a contrast agent. , It should be noted that silica and gold based hybrid structures have been recognized as translational materials for clinical trials. Although an integration of these two components seems logically promising for exceptional theranostics, several hurdles make it a challenge. , Silica coating is a versatile approach for maintaining the thermal and chemical stability, optical property, and aspect ratio of metal nanoparticles, especially gold nanorods, which also makes them applicable for drug delivery, photothermal therapy, photoacoustic imaging, sensing, etc. Although using a nonporous silica coating to maintain t...…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…For example, at low temperature (<65 °C) and stirring, a large network is formed due to the slow rate of hydrolysis and condensation for silica formation, whereas higher temperature (60–80 °C) and vigorous stirring result in mesostructured particles in the nanometer range. It is reported that aggregated and large clumps of silica particles are formed beyond 80 °C of reaction temperature. ,, On the other hand, the slow rate of silicification at low acidity and high ionic strength is well documented in the literature. , Cationic surfactant CTAB assembled in a hexagonal array, which helps in creating 2D pores/channels with an interchannel distance of about 4 nm followed by base-catalyzed hydrolysis–condensation of an orthosilicate precursor (source of silica particle formation) for mesoporous silica network formation, which are characteristics of MCM-41 type silica. Silica nanoparticles are also prepared by using TEA as a sterically bulky chelating agent (pH stabilizer and as an additive) that controls the particle diameter . Later, surface modified mesoporous silica nanoparticles with various small molecules have been reported for biomedical applications, either imaging or therapeutics of cancer. , Silica is a well understood biomaterial and claimed as a safe material for preclinical and clinical studies. , Obviously, silica, especially MS, is inferior as a contrast agent. , It should be noted that silica and gold based hybrid structures have been recognized as translational materials for clinical trials. Although an integration of these two components seems logically promising for exceptional theranostics, several hurdles make it a challenge. , Silica coating is a versatile approach for maintaining the thermal and chemical stability, optical property, and aspect ratio of metal nanoparticles, especially gold nanorods, which also makes them applicable for drug delivery, photothermal therapy, photoacoustic imaging, sensing, etc. Although using a nonporous silica coating to maintain t...…”
Section: Introductionmentioning
confidence: 96%
“…45,50−56 Several attempts including Gorelikov and Matsuura's method require 10 h to 3 days; 31−47,50−56 however, they are limited with poor product yield (∼10 mg) 40 and moderate surface area (∼641 and 934 m 2 /g). 43,44,47,57 Disordered pores and thin silica shells (13−30 nm) 47 significantly reduce the drug loading efficacy of GMS nanoparticles, which is about 25 ± 1.5%. 58 Further, the scalability has always been a bottleneck for such hybrid structures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The localized surface plasmon resonance (LSPR) of metal nanoparticles has been used in biomedical applications, sensors, catalysis, and surface-enhanced spectroscopy [1][2][3][4][5]. Unlike metal nanoparticles, the LSPR of doped semiconductor nanocrystals (NCs) can be modulated by changing the doping content.…”
Section: Introductionmentioning
confidence: 99%